Isolation of pathogens from tracheal infection of intensive care unit admitted patients and analysis of antibiotic susceptibility - Haque, Sabrina (BRAC University, 2021)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Microbiology, 2021.